Fossilization in second language acquisition: some experimental data from the second language classroom - Hammond, Robert M. (Lenguas Modernas, 2017)
Higgs and Clifford (1982) claim that grammatical accuracy must be stressed before communicative modes of language instruction can be undertaken. Implicit in this article is that grammar must be taught deductively and that students taught second languages through the use of communicative models, in which grammar is inductively taught, do not learn grammar. In this study, experimental sections of first semester Spanish courses were taught using the natural approach methodology and control sections were taught by instructors using a modified grammar-translation methodology including deductive grammar instruction. Students from all sections took the same department-administered discretepoint exams. The data presented herein show that the experimental sections out-performed the sections taught by traditional grammar-translation methods.